Optimization of Technology of Canned Meat Products - BAL’-PRYLYPKO, L.; SLOBODIANIUK, N.; BRONA, G.; MOROZIUK, R.; AL’ RAVASHDEKH, A. (Journal of Education, Technology and Computer Science, 2017)
It was determined the parameters of quality of functional canned mince meat productsoptimized by adding of preparations of proteins of blood plasma (2%) and cellular tissues (2.5%), and developed the optimized technology of their production.